OPENING OF CARBOHYDRATE 5,6-EPOXIDES WITH CHIRAL ACETATE AND PROPIONATE ENOLATE EQUIVALENTS ATTACHED TO THE IRON CHIRAL AUXILIARY [C5H5)FE(CO)(PPH(3))] - Davies, S; Kellie, H; Polywka, R (1994)
The lithium enolate derived from the chiral iron acetyl complex (RS)-[(C5H5)Fe(CO)(PPh3)COCH3] (RS)-1 opens, in the presence of boron trifluoride etherate, the carbohydrate 5,6-epoxides, 5,6-anhydro-3-O-benzyl-1,2-O-isopropylidene-α-D-allofuranose 3, 5,6-anhydro-3-O-benzyl-1,2-O-isopropylidene-β-L-talonofuranose 4, 5,6-anhydro-3-O-benzyl-1,2-O-isopropylidene-α-D-glucofuranose 5, and 5,6-anhydro-3-O-benzyl-1,2-O-isopropylidene-β-L-idofluranose 6 to generate after decomplexation the doubly homologated γ-lactones 3-O-benzyl-6,7-dideoxy-1,2-O-isopropylidene-α-D-allo-octafuranurono-5,8-lactone 15, 3-O-benzyl-6,7-dideoxy-1,2-O-isopropylidene-β-L-talono-octafuranurono-5,8-lactone 16, 3-O-benzyl-6,7-dideoxy-1,2-O-isopropylidene-α-D-gluco-octafuranurono-5,8-lactone 17, and 3-O-benzyl-6,7-dideoxy-1,2-O-isopropylidene-β-L-ido-octafuranurono-5,8-lactone 18 respectively. The lithium enolate derived from the homochiral iron propionyl complexes (R)-[(C5H5)Fe(CO)(PPh3)COCH2CH3] (R)-2 and (S)-[(C5H5)Fe(CO)(PPh3)COCH3] (S)-2 convert after decomplexation 5,6-anhydro-3-O-benzyl-1,2-O-isopropylidene-α-D-glucofuranose 5 to 7(R)-methyl-3-O-benzyl-6,7-dideoxy-1,2-O-isopropylidene-α-D-gluco-octafuranurono-5,8-lactone 20 and 7(S)-methyl-3-O-benzyl-6,7-dideoxy-1,2-O-isopropylidene-α-D-gluco-octafuranurono-5,8-lactone 22 respectively. © 1994.